Using the ICTs in Distance Education: the Virtualization process at UNED - Carreras, C.; Yuste, M.; Sánchez, J. P. (Revista Cubana de Física, 2007)
A few years ago, the National University for Distance Education (Universidad Nacional de Educación a Distancia, UNED) started the “virtualization” process of all its official studies in an attempt to take advantage of the great possibilities of the new information technologies. This tendency, very popular in almost every university all around the world, becomes fundamental in a distance-learning university like UNED. In this work, we describe in detail the concept, structure and contents of the so called “UNED Virtual Courses”.